A moving mesh FE methodology for vehicle–bridge interaction modeling. Issue 14 (15th July 2020) - Greco, Fabrizio; Lonetti, Paolo; Pascuzzo, Arturo
Abstract: A numerical strategy based on a moving mesh technique is proposed to simulate vehicle–bridge interaction (VBI) in railway bridges. ALE approach allows an easy description of the VBI, which is essentially based on a proper rezoning method. Contrarily to classical moving mesh methods the definition of the structural problem is not modified, leading to an easy approach to be endorsed in classical FE procedures. Numerical results in 3D straight and curved bridges are proposed for the validation. Moreover, a parametric study is developed for a 3D bridge structure, in which several bridge deck descriptions and vehicle loads are investigated.